Karakteristik Bubuk Instan Cemcem ( spondiaz pinnata lf kurz ) - Luh Putu Wrasiati; I Nyoman Semadi Antara; Ni Made Wartini (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2014)
One of tropical plant used as a traditional beverage in Bali is Kecemcem or Cemcem (Spondias pinnata (Lf) Kurz) or in Indonesian called Kedondong Hutan. Empirically, the beverage is mentioned for treating coughs, increasing appetite, and body refreshment. Besides used as a beverage, Cemcem leafs are also used as a flavor enhancer of fish products. The study was carried out to determine the characteristics of Cemcem instant powder produced by encapsulation using maltodextrin and dried by the thin layer drying method. Cemcem instant powder was then analyzed its content of vitamin C, total phenols, tannins, antioxidant capacity, water cntent, ash content, and solubility. The flavor compounds in Cemcem instant powder obtained in Bukit Jimbaran area are identified by GC-MS devices. The result showed that cemcem instant powder which was produced by 24 hours of maceration time has the best characteristics and potential to be developed as a natural antioxidant products. It has the highest of total phenol, tannin, vitamin C, and antioxidant capacity. The content of vitamin C, total phenol, and tannin were 135.06 mg/100g, 38.95 mg GAE/g, and 11.01% respectively. The antioxidant activity of cemcem instant powder which analyzed by DPPH method was about 43.80%. There are 17 compounds detected by GC-MS, these compounds belonged alkenesalcoholsphenols compounds and esters of fatty acidsThe whole compounds were the building blocks of flavor cemcem leaves.Keywords : Characteristic of cemcem instant powder, antioxidant capacity, andflavor compounds of cemcem leaves